2010
DOI: 10.1074/jbc.m110.101543
|View full text |Cite
|
Sign up to set email alerts
|

Prodrug Activation by Cryptosporidium Thymidine Kinase

Abstract: Cryptosporidium spp. cause acute gastrointestinal disease that can be fatal for immunocompromised individuals. These protozoan parasites are resistant to conventional antiparasitic chemotherapies and the currently available drugs to treat these infections are largely ineffective. Genomic studies suggest that, unlike other protozoan parasites, Cryptosporidium is incapable of de novo pyrimidine biosynthesis. Curiously, these parasites possess redundant pathways to produce dTMP, one involving thymidine kinase (TK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…A previous study demonstrated the ability of C. parvum thymidine kinase to activate pyrimidine analogs including floxuridine. Additionally, trifluoromethyl thymidine (TFT; another fluoropyrimidine) exhibited efficacy in a mouse model of acute C. parvum infection (22). Furthermore, widespread use of nucleoside analogs in the prevention of motherto-child transmission of HIV (23) suggests that certain formulations of the chemical family are safe for use in pediatric populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated the ability of C. parvum thymidine kinase to activate pyrimidine analogs including floxuridine. Additionally, trifluoromethyl thymidine (TFT; another fluoropyrimidine) exhibited efficacy in a mouse model of acute C. parvum infection (22). Furthermore, widespread use of nucleoside analogs in the prevention of motherto-child transmission of HIV (23) suggests that certain formulations of the chemical family are safe for use in pediatric populations.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen of the 21 confirmed compounds identified by our screen are currently FDA approved for use in patients, but only five of these compounds, floxuridine (22), clofazimine (46), indomethacin (47), minocycline (48,49), and doxycycline (50), are described in the literature as having activity against Cryptosporidium species in vitro or in vivo (animal models or human patients), suggesting that the list is rich in new repurposing candidates. While we chose to pursue the HMG-CoA reductase inhibitor itavastatin, we have made the screening results of all 727 compounds available as supplemental data, which we hope will inform additional studies aimed at repurposing drugs for cryptosporidiosis and other apicomplexan infections as well as elucidate apicomplexan biology and novel host-microbe interactions.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that the inactive compounds A110 and P83 displayed the best plasma pharmacokinetic behavior, while the active compounds P96 and P131 have relatively poor systemic exposure. In vivo anticryptosporidial activity has also been reported for several other compounds with poor systemic bioavailability, most notably paromomycin, and also including pyrvinium pamoate, dication carbazoles, and trifluoromethylthymidine (15,20,25). While nitazoxanide exhibits good systemic exposure, its active metabolite tizoxanide is efficiently recycled to the intestine via glucuronidation (12).…”
Section: Discussionmentioning
confidence: 94%
“…Paromomycin is effective in rodents and has also been used to treat cryptosporidiosis, though a significant benefit has not been demonstrated in humans (13). Approximately 20 additional compounds have displayed at least some anticryptosporidial activity in animal models (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Unfortunately, as with nitazoxanide, the targets of most of these compounds have not been identified, which makes further development difficult.…”
mentioning
confidence: 99%
“…Among the available options, the wheat germ system is robust, it quickly produces high yields, and it is scalable and cost-effective. Previously, we demonstrated the successful cell-free expression of very challenging parasite enzymes in fully functional form: P. falciparum dihydrofolate reductase-thymidylate synthase (PfDHFR-TS) and Cryptosporidium parvum thymidine kinase (20,21). The cell-freeproduced DHFR-TS had all three known functions of native protein: DHFR catalytic activity, TS catalytic activity, and autologous RNA binding (20).…”
mentioning
confidence: 99%